IOT BASED CAR PARKING MANAGEMENT SYSTEM USING CAR PLATE RECOGNITION - Yip, Zhi Chuan (Universiti Malaysia Sarawak (UNIMAS), 2019)
Nowadays, car parking is a major issue in modern congested cities. There are too many vehicles on the road that leads to high demand for vehicles parking, especially in the central business district. The rapid growth of the Internet of Thing (IoT) was lead to a more robust IoT platform. These IoT platforms provide higher processing power that allows the implementation into the more complicated application. Hence, an IoT based car parking management system using car plate recognition is proposed. These proposed systems provide a low-cost solution for the current parking management system. The IoT platform for this system is Raspberry Pi. Moreover, the use of the Raspberry Pi camera is used to capture car image and the proximity sensor is used as a sensor to detect the presence of a vehicle. This project uses the Open ALPR API as the vehicle plate recognition and extraction algorithm. Nonetheless, this proposed system introduces an online parking fee payment platform.